Abschiedsworte am Sarge Albert Wilhelm Kafemanns von H. Rickert. - Rickert, Heinrich (1833-1902) ([s.n.], 1891)
Druk z mową pożegnalną na pogrzeb znanego drukarza gdańskiego A.W. Kafemanna 7.01.1891 r.